Pewarnaan Sisi r-Dinamis pada Graf Khusus dan Graf Operasi Sakel - Viqedina Rizky Noviyanti; Kusbudiono Kusbudiono; Ika Hesti Agustin; Dafik Dafik (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2021)
Let $G=(V(G),E(G))$ be a nontrivial connected graph. The edge coloring is defined as $c:E(G) → \{1,2,...,k\}, k \in N$, with the condition that no adjacent edges have the same color. k-color r-dynamic is an edge coloring of k-colors such that each edge in neighboring $E(G)$ is at least min $\{r,d( u)+d(v)-2\}$ has a different color. The dynamic r-edge coloring is defined as a mapping of $c$ from $E(G)$ such that $|c(N(uv))|$ = min$\{r,d(u)+d(v)- 2\}$, where $N(uv)$ is the neighbor of $uv$ and $c(N(uv))$ is the color used by the neighboring side of $uv$. The minimum value of $k$ so that the graph $G$ satisfies the k-coloring r-dynamic edges is called the dynamic r-edge chromatic number. 1-dynamic chromatic number is denoted by $λ(G)$, 2-dynamic chromatic number is denoted by $λ_d(G)$ and for dynamic r-chromatic number is denoted by $λ_r(G)$. The graphs that used in this study are graph $TL_n$, $TCL_n$ and the switch operation graph $shack(H_{2,2},v,n)$.